Influência da pandemia para os trabalhadores da educação: o caso de uma instituição federal de ensino superior - Lima, Mônica Tavares França de (Universidade do Vale do Rio dos Sinos, 2022)
The COVID-19 pandemic has caused changes in the routines of professionals around the world. Especially in education, the teaching of students and the work of professionals, teachers and technicians were affected by these changes. In this sense, the following work is proposed, whose general objective is to analyze the influences of COVID-19 on the work routine of education professionals, in the context of a federal public university, as well as to propose strategies for managing people that contribute to health. and the well-being of these professionals. Regarding the methodology, this research is characterized by being a case study with a qualitative approach. The data collection instruments used are: the electronic questionnaire and the semi-structured interview. Data collection was carried out in 2021. Data analysis is done using the content analysis methodology. We can infer from this study that the pandemic physically and psychologically affected education workers. Due to social isolation, the lack of socializing with colleagues, as well as personal relationships were harmed. Also, the organization of time became a challenge for education workers, who in addition to the increase in work and workload, had to adapt to remote teaching and work. Identifying sources of psychosocial risk that can lead education workers to stress and illness, during and after the pandemic, is an important task for managers. Thus, it is necessary to adopt protective measures, capable of reducing the impacts of COVID-19 on the physical and mental health of workers, especially in the work of education professionals, providing more quality of life.
Keywords: Pandemia; Trabalhador da educação; Educação superior; Ensino remoto; Pandemic; Education worker; College education; Remote teaching; ACCNPQ::Ciências Humanas::Educação